DEVELOPMENT OF NEW EQUATIONS FOR ESTIMATING GROSS CALORIFIC VALUE OF INDONESIAN COALS - Miftahul Huda (Puslitbang tekMIRA, 2014)
Numerous empirical equations have been published to correlate the gross calorific value (GCV) of coals with the result of proximate or ultimate analysis, however, many researchers continue to propose new equations. One of the reasons is that many existing equations are likely fitted to coal of one region only. This study is aimed to evaluate the applicability of some existing equations to calculate GCV of Indonesian coal and to develop new equations that more accurate to predict the calorific value of Indonesian coal. Ten (10) new GCV formulas based on proximate analysis data of Indonesian coal were generated using SPSS software. They include three (3) equations with one independent variable, four (4) equations with two independent variables, two (2) equations with three independent variables and one (1) equation with four independent variables. The best equation has the following form: GCV= 25.284 (M) + 30.572 (Ash) + 62.127 (VM) + 138.117 (FC) - 2890.095. The result is in agree with previous work that equation involving four independent variables i.e. moisture (M), ash, volatile matter (VM) and fixed carbon (FC) provides the most accurate estimation of GCV. The new equation when it is used for calculating GCV of Indonesian coals gives more accurate results than that of some existing equations in the literatures.